Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.4314/jsda.v16i2.23876
|View full text |Cite
|
Sign up to set email alerts
|

The education of girls and women in Uganda

Abstract: The African e-Journals Project has digitized full text of articles of eleven social science and humanities journals. This item is from the digital archive maintained by Michigan State University Library.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Schools are the places where some of the dearly held Phatudi "You should give a child love and take them warm-heartedly from their parent" beliefs and traditions of the community can be challenged by not accentuating differences. Accentuation of these differences is congruent with results of studies that have found that girls leave school early to get married or are pushed out of school because they cannot cope with schoolwork due to the demands made upon them at their homes (Atekyereza, 2001). …”
Section: Recommendations and Conclusionsupporting
confidence: 77%
See 2 more Smart Citations
“…Schools are the places where some of the dearly held Phatudi "You should give a child love and take them warm-heartedly from their parent" beliefs and traditions of the community can be challenged by not accentuating differences. Accentuation of these differences is congruent with results of studies that have found that girls leave school early to get married or are pushed out of school because they cannot cope with schoolwork due to the demands made upon them at their homes (Atekyereza, 2001). …”
Section: Recommendations and Conclusionsupporting
confidence: 77%
“…According to Crespi (2003), gender socialisation is a process that teaches children what it means to be a boy or girl. Atekyereza (2001) says that promoting gendered roles in Uganda had a negative effect of polarising roles with an adverse effect on their identity and self-esteem. He furthermore says that socialisation is tantamount to being subjected to "pressures -rewarding, punishing, -that push the child towards evoking certain acceptable responses" (Atekyereza, 2001:118).…”
Section: Figure 1: Boys Packing Away Chairs and Girls Packing Away Mamentioning
confidence: 99%
See 1 more Smart Citation
“…In Uganda, sociocultural. economic, policy and political obstacles to the education of women were found to explain the lower rates of female school enrolment (Atekyereza 2001). Families may give greater priority to boys' education while traditional customs pertaining to the social status of women may have become incorporated into the economic and political framework, thereby inadvertently interrupting their schooling.…”
Section: Discussionmentioning
confidence: 98%
“…Related to that, parents or caregivers generally prefer sending boys to school since the education benefits for a girl are enjoyed by the family into which she marries and not her family of origin (Atekyereza, 2001). Additionally, the HIV/AIDS pandemic in sub-Saharan Africa and the resulting illnesses and deaths of the adults in the household, create the need for girls to stay home from school to help take care of sick relatives and smaller siblings, and perform overall household duties in the context of ill or deceased caregivers.…”
Section: Education and Gender In Ugandamentioning
confidence: 99%